A SEMIOTIC ANALYSIS ON THE HELP MOVIE POSTERS - RAHMASARI, INDAH (Jurnal Ilmiah Mahasiswa FIB, 2014)
Rahmasari, Indah. 2014. A Semiotic Analysis on The Help Movie Posters.Study Program of English, Department of Languages and Literature, Faculty ofCultural Studies, Universitas Brawijaya. Supervisor: Yana Shanti Manipuspika;Co-Supervisor: Emy SudarwatiKeywords: semiotics, movie poster, sign, denotation, connotation, myth. Movie posters normally contain many kinds of verbal and visual signs.The images with text that appear in the movie poster inform the viewer aboutwhat approximately happened along the story. It reflects the main idea of the story in the movie. In this research, the researcher used verbal and visual signs found in movie posters from racism theme movie entitled The Help as the main data. They consist of two The Help official movie posters which were launched byDreamWorks Studio and The Help reprint movie posters were designed by posterartists or graphic designers that versed in designing a movie poster. There arethree problems of the study that are answered in this research, they are: (1) What are the denotative signs found in The Help movie posters; (2) What are the connotative signs found in The Help movie posters; and (3) What are the myths built in The Help movie posters.Since the main data were taken from movie posters, qualitative researchwith content or document analysis was used in this research to describe thephenomena. In analyzing the data, the researcher used Barthes theory (1972) to build the meaning through denotation and connotation theory and how it is then bringing them into a myth that people believed as racism issues in The Help movie posters.The denotative signs found in this research are from the representation of visual and verbal elements in the posters such as the title, tagline, and the image of women, gestures, and facial expression, the image of bench, pigeon, ravens, cage, cartoon, and also colors. While connotation is used to build the meaning behind each of denotative signs found in the movie posters such as the way the citizens of America face the racism issues based on the skin color differences. The myth built in the movie posters consider White people as the best race between others is pictured in the fifth of The Help movie posters.Related to this study, the researcher suggests the next researcher to analyzeanother object like videos, movie or any motion picture. The use of differenttheories is also suggested for the next researcher to expand the knowledge about semiotic study.